The Role of Albumin in the Diagnosis of Neonatal Sepsis Over the Last 11 Years: A Retrospective Study - Shi J; Lu ZQ; Lin QM; Zeng W; Gu PJ; Yu Q; Long J; Huang DG; Dai YH (Dove Medical Press, 2023)
Jipeng Shi,1 Zhen-Qi Lu,1 Qing-Mei Lin,2 Wang Zeng,1 Ping-Jiao Gu,1 Qing Yu,3 Jing Long,1 Da-Gui Huang,1 Yi-Heng Dai1 1Department of Neonatal, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University (Foshan Maternity & Child Healthcare Hospital), Foshan, Guangdong, 528000, People’s Republic of China; 2Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University (Foshan Maternity & Child Healthcare Hospital), Foshan, Guangdong, 528000, People’s Republic of China; 3Department of Clinical Laboratory, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University (Foshan Maternity & Child Healthcare Hospital), Foshan, Guangdong, 528000, People’s Republic of ChinaCorrespondence: Yi-Heng Dai, Email daiyiheng@163.comBackground: There are many difficulties and uncertainties in the early diagnosis of neonatal sepsis. The aim of this study was to determine whether albumin (ALB) is useful for the early diagnosis of neonatal sepsis using ALB, C-reactive protein (CRP) and procalcitonin (PCT) together.Methods: ALB, CRP, PCT and white blood cell (WBC) data from 732 patients with neonatal sepsis and 1317 neonatal infection patients hospitalized in Foshan Maternal and Child Health Hospital from 2011 to 2022 were collected. Receiver operating characteristic (ROC) and logistic regression analyses were performed to assess the diagnostic value of ALB, CRP, PCT and the WBC count for neonatal sepsis. The roles of ALB, CRP, PCT and the WBC count in the diagnosis of neonatal sepsis were analysed by using subject working characteristics (ROC) and areas under the curve (AUCs), and the variables were combined to determine which combination had the best diagnostic efficacy.Results: In the sepsis group, the ALB, CRP, and PCT levels and the WBC count were significantly higher than those in the infection group (P< 0.001). In all infants, the sensitivities and specificities of ALB, CRP, PCT, and WBC count were 0.411, 0.596, 0.483 and 0.411, respectively, and 0.833, 0.846, 0.901 and 0.796, respectively. With a sensitivity of 0.646, a specificity of 0.929, and an AUC of 0.834, the best combination was that of ALB, CRP, and PCT, which was better than that of CRP + PCT, CRP + ALB and PCT + ALB.Conclusion: In neonatal sepsis, in the absence of blood culture results, the combination of ALB, CRP, and PCT is more reliable than CRP, PCT, or CRP+PCT alone. These results suggest that ALB is a useful inflammatory biomarker for the early diagnosis of neonatal sepsis, and can improve the diagnostic efficiency.Keywords: albumin, C-reactive protein, procalcitonin, diagnosis, neonatal sepsis